Incorporating sardine cooking water aromas into plant-based diets for European seabass - Resende, Daniela (2024)
Funding Information: This work was supported by Project “MobFood – Mobilizing scientific and technological knowledge in response to the challenges of the agri-food market” (POCI-01–0247-FEDER-024524), financed by ERDF, through PORTUGAL2020/COMPETE2020/ Lisb@2020. Publisher Copyright: © 2024